Legal Protection of Personal Data of Telecommunication Users for Prepaid Card Registration at Grapari Tritura Medan - Rangkuti, Muhammad Fiqri; Ahmad, Akiruddin; Akmal, Akmal (Judge : Jurnal Hukum, 2024)
The purpose of this study is to determine the form of legal protection of personal data of telecommunication service users regarding the implementation of prepaid card registration requirements and the legal consequences of the existence of prepaid card registration requirements. This research is a unique approach to the legislation contained in Law No. 8 of 1999 on Consumer Protection, Law No. 24 of 2013 and Law No. 36 of 1999 on Population Management. Minister of Communication and Informatics Regulation on Telecommunication and Minister of Communication and Informatics Regulation No. 20/2016 on Personal Data Protection in Electronic System, Minister of Communication and Informatics Regulation No. 12/2016 on Telecommunication Service Customer Registration, Minister of Transportation Regulation No. 21/2017. Telecommunication service providers are obliged to keep customer data as long as the customer is still actively subscribing to telecommunication services.